Вплив кута випередження запалювання на показники роботи двигуна, обладнаного сучасною системою впорскування бензину - Славін, Віктор Васильович; Гунько, Андрій Веніамінович; Головня, Сергій Борисович (Національна академія Державної прикордонної служби України ім. Богдана Хмельницького, 2014)
Одним з експлуатаційних факторів, який впливає на робочий процес згоряння в двигунах з іскровим запалюванням, є кут випередження запалювання θ (град). При обладнанні карбюраторних двигунів в умовах експлуатації сучасною електронною системою впорскування бензину, в якій кути випередження запалювання призначені для базового двигуна і змінюються статичною електронною системою запалювання, необхідно визначити оптимальні θ, призначені для двигуна іншої конструкції.

One of the operational factors that affect the working process of combustion in spark-ignition engines is the ignition angle θ (deg). The optimum ignition timing is determined for each type of engine on the brake test stand, and it is known that the deviation angle from the optimum ignition timing leads to a shift of the indicator diagram relative to the upper dead point and increasing the heat losses. In laboratory tests the engines of the National Transport University carries out activities designed to reduce environmental pollution by toxic substances of exhaust gases and fuel consumption of petroleum origin wheeled vehicles. Between them, promising is the use of modern electronic system of fuel injection and exhaust after treatment on cars in service with petrol engines. For comparative studies using common carburetor engine 4F7,6/6,6, which is equipped with modern electronic system of fuel injection distributed feedback type LH-Motronic. Process the results of research in high-speed and load conditions of the engine 4F7,6/6,6 with different power systems from the values of angles ignition timing of the engine with carburetor system determines the value of new angles ignition engine equipped in conditions of modern electronic fuel injection. Conducting research performance engine 4F7,6/6,6 with different power systems and new angles ignition speed and load conditions. Experimental research engine with various system of feed have shown that changing the base ignition timing angles in the program control engine fuel injection system contributed to decrease in of fuel consumption on characteristics of idling by 11%, the specific fuel consumption average and loading (n = 2000 min-1) characterization of the injection system decreased by 5 %. Engine power of the fuel injection system at full load increased by 6,6 %.
Influence of ignition timing on the performance of the engine is equipped with modern system of fuel injection
Keywords: карбюратор; система електронна; іскра; згоряння детонаційне